Beyond eco-efficiency in the built environment / Kelley Beaverford - Beaverford, Kelley (2012)
Sustainability, in the fields of architecture, is often understood as eco-efficiency but this paper explores how an international service learning course can promote a broader definition of sustainability that includes cultural, humane and political aspects. To do this, it will integrate a literature review with the author's experience teaching an international design build studio. The intention of the paper is to encourage discussion on how we can move beyond mere eco-efficiency in design education towards a broader definition that also consider our responsibilities as global citizens.